Synthesis and Performance Evaluation of a Novel Natural Surfactant Polymer Assembly for Enhanced Oil Recovery - Machale, Jinesh Subhash (Curtin University, 2022)
The chemical method of enhanced oil recovery (EOR) has immense scope in the oil field. Recently, many researchers have been looking for the natural surfactants and exploring their potency in EOR. The main target of this research work is to synthesize a natural surfactant from Eichhornia crassipes weed for EOR. Numerous analyses such as the measurement of interfacial, adsorption, rheological, and core flooding are carried out to study the performance of the developed natural surfactant.